2014
DOI: 10.1089/cyber.2014.0198
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Pain Management in Cardiac Surgery

Abstract: Surgical anxiety creates psychological and physiological stress, causes complications in surgical procedures, and prolongs recovery. Relaxation of patients in postoperative intensive care units can moderate patient vital signs and reduce discomfort. This experiment explores the use of virtual reality (VR) cybertherapy to reduce postoperative distress in patients that have recently undergone cardiac surgery. Sixty-seven patients were monitored at IMSS La Raza National Medical Center within 24 hours of cardiac s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 15 publications
1
68
1
3
Order By: Relevance
“…Our pilot also revealed side effects in approximately 25% of women. This rate is paradoxically higher in comparison to similar VR studies which have demonstrated side effects from the intervention to be between 0-5% 15,35,36 . However, these rates were similar in both, the control and intervention groups, leading us to attribute this phenomena to the terbutaline employed in the study.…”
Section: Discussioncontrasting
confidence: 63%
“…Our pilot also revealed side effects in approximately 25% of women. This rate is paradoxically higher in comparison to similar VR studies which have demonstrated side effects from the intervention to be between 0-5% 15,35,36 . However, these rates were similar in both, the control and intervention groups, leading us to attribute this phenomena to the terbutaline employed in the study.…”
Section: Discussioncontrasting
confidence: 63%
“…Rationale: Cybertherapy is a VR distraction postulated to reduce postoperative pain and distress in the ICU. A set of five simulated environments was displayed to the patient for 30 minutes before and after surgery (126). Hypnosis was administered by a trained ICU nurse in alert ICU patients and was induced using the cenesthesic approach (i.e., patient attention focused on any body sensation) or carried out on the actual symptom (pain or anxiety) (127).…”
Section: Nonpharmacologic Interventions To Reduce Pain Cybertherapy/hmentioning
confidence: 99%
“…Hypnosis was administered by a trained ICU nurse in alert ICU patients and was induced using the cenesthesic approach (i.e., patient attention focused on any body sensation) or carried out on the actual symptom (pain or anxiety) (127). One study evaluated 67 postcardiac surgery ICU patients before and after the cybertherapy intervention (126). Most (88%) reported a decreased level of postoperative pain (MD, -3.75 cm on the 0-10 VAS) that corresponded to a change from "severe to moderate" to "moderate to light" pain.…”
Section: Nonpharmacologic Interventions To Reduce Pain Cybertherapy/hmentioning
confidence: 99%
“…Monitoring physiological arousal is increasingly becoming an integral feature of virtual reality therapy (VRT) for pain management (see Table 1). Mosso and colleagues demonstrated the link between autonomic responses to pain and patients' respective subjective ratings [37]. This study found positive correlations between physiological measurements, such as respiration rate and heart rate, and subjective Likert scale ratings of pain in patients who had recently undergone cardiac surgery.…”
mentioning
confidence: 67%
“…For more than twenty years, healthcare specialists, from physicians to psychologists, have supplemented treatments and surgeries and even implemented preventative methods using VR [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Researchers and clinicians have applied VR as a supplementary tool to treat behavioral disorders and phobias [39,40], reduce anxiety [22], and manage chronic pain in patients [25,27,28,[32][33][34][35][36][37][38]. These interventions underscore the widespread applicability of VR to serve as an adjunctive pain management tool in a variety of healthcare procedures.…”
mentioning
confidence: 99%